Budding adult hypertensives with modifiable risk factors: "Catch them young" - Aravind S.K. Ramanathan; Prabha Senguttuvan; Vel Prakash; Appasamy Vengadesan; Rajendiran Padmaraj (Wolters Kluwer Medknow Publications, 2016)
Background: Since the data of primary hypertension (HT) in children is scanty in India, this study attempted to evaluate HT by a multidimensional investigation of the various risk factors in children and adolescents. Materials and Methods: A total of 3906 subjects were recruited, all of whom lived in Chennai, an urban area of Tamil Nadu. The children and adolescents aged from 10 to 17 years were selected by random sampling. The children/adolescents were randomized into one control and further divided into two groups. The National High Blood Pressure Education Program fourth report (2004) and anthropometric body mass index (BMI), food frequency questionnaire (PURE) were followed in the study. Results: Out of 3906 children, 2107 were girls and 1799 boys. On screening, we found 9.5% to be hypertensive with the prevalence rate of boys and girls 8% and 10.8%, respectively. Overall obesity was 2.7%, (boys 2%, girls 3.32%); hypertensives and normotensives were 8.4% and 2.1%, respectively. We found that overweight (odds ratio [OR]: 2.06 [1.40-3.01] 95% confidence interval [CI]), obese children (OR: 1.21 [2.72-6.48] 95% CI), and those with a family history of HT (OR: 1.66 [1.20-2.30] 95% CI) had increased risk of hypertension. Females were 1.39 times (OR: 1.39 [1.11-1.72] 95% CI) more at risk of getting HT. Multivariate analysis showed that obese children/adolescent were four times more likely to have HT than children with normal BMI (OR: 4.67 [3.00-7.26] 95% CI]. Conclusion: Family history of HT, obesity, and female gender are associated with a high risk of HT. The prevalence of HT was higher among obese adolescents than among slender subjects. This may be related to their sedentary lifestyle, faulty eating habits, high fat content in the diet and little physical activity.